Covid-19 and adult learning in Nigeria: can technology help? an exploration of adult literacy facilitators’ perspective (2022)
The outbreak of COVID-19 and its impact on learning globally cannot be overemphasized. Specifically, the pandemic severely affected adult learning and these further compounded issues bedeviling literacy promotion, especially in developing nations like Nigeria. This study assessed the impact of COVID-19 on adult learning and the place of technologies in facilitating adult learning in Nigeria. A qualitative research method through the lens of the interpretive paradigm was adopted for this study. The study is underpinned by the Theory of Andragogy and the Technology Acceptance Model. An in-depth interview with forty-six adult literacy facilitators across selected states in the country forms the participants of the study. The interview transcript was analyzed using a thematic framework. Findings revealed amongst others that COVID-19 impaired adult learning significantly in Nigeria. There exists a strong belief among literacy facilitators in the country that technologies can be used as an instructional delivery mechanism for learners in adult literacy programmes. Thus, radio, television, and mobile phone ranked 1st, 2nd, and 3rd respectively among suggested technological tools to facilitate adult learning in Nigeria. Based on the findings, it was suggested that there is a need for literacy stakeholders in the country to rethink adult literacy delivery modalities beyond the traditional approach. Also, it is suggested that enabling environment should be provided and familiar technologies such as radio, television and mobile phones should be used with adequate guidance and encouragement to improve learners’ access and participation in literacy programmes. While technology is not the silver bullet that will solve obstacles facing access to and participation in adult literacy programmes, there is a need to explore opportunities in the use of technologies to facilitate adult learning in Nigeria.